Use of solid urban waste at the Technological Institute of Toluca - Isaías de la Rosa Gómez; Jesús Alfredo Liévanos Barrera (Universitas Diponegoro, 2022)
Solid Urban Waste (SUW) and Special Handling (EHW) generated in the Institution are handled in 200-liter plastic containers with the appropriate identification according to the type of waste and the race, placed in the buildings of each of the races; the waste is separated by the students following the criterion of the 4 Rs (Reduce, reduce, reuse and recycle). Reusable waste is used for students to make different products in the reuse workshop of the Institutional Environmental Program (IEP) such as paper pads, acetate pencil holders, pens, paper holder and paper board, among others for use by the Institution's population. With the organic waste (OR) compost is prepared in the composting center, which is used to fertilize the green areas. The recyclable waste is sold obtaining an economic benefit that allows the operation of the activities carried out by the (IEP). The (EHW) are concentrated in the “green point” to be sent to the “recyclers”. The alkaline batteries, the Institution collects them temporarily, giving the service to the population of the Toluca valley to be sent to confinement by the municipality of Toluca. The use of Solid Urban Waste allows to form a sustainable environmental culture in the population of the Institution, such as savings in the consumption of paper, financing in the operation of the (IEP) and supporting the economy of the students.Keyword: Solid waste, paper, composting, reuse, recyclable